2012
DOI: 10.3390/bs2010038
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Effects of Upper Respiratory Tract Illnesses: A Consideration of Possible Underlying Cognitive Mechanisms

Abstract: Previous research has shown that both experimentally induced upper respiratory tract illnesses (URTIs) and naturally occurring URTIs influence mood and performance. The present study investigated possible cognitive mechanisms underlying the URTI-performance changes. Those who developed a cold (N = 47) had significantly faster, but less accurate, performance than those who remained healthy (N = 54). Illness had no effect on manipulations designed to influence encoding, response organisation (stimulus-response c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Results from two studies showed that having a cold was associated with reduced alertness and psychomotor slowing. Other research has confirmed that memory accuracy is not impaired in individuals with colds (Bucks et al, 2008;Smith, 2012b).…”
Section: Naturally Occurring Urtismentioning
confidence: 86%
“…Results from two studies showed that having a cold was associated with reduced alertness and psychomotor slowing. Other research has confirmed that memory accuracy is not impaired in individuals with colds (Bucks et al, 2008;Smith, 2012b).…”
Section: Naturally Occurring Urtismentioning
confidence: 86%
“…Sleep disturbance is another major issue, which is frequently encountered in patients with respiratory tract infections. 15 Sleep disturbance is known to be directly linked to nasal and sinus congestion. 16 Thus, a significant reduction in several patients with sleep disturbances in Emtact arm in the present clinical trial signifies a substantial reduction in nasal and sinus congestion.…”
Section: Discussion Principal Findings Of the Studymentioning
confidence: 99%
“…This was achieved 46,47 , and some of the studies even used virological techniques to identify the infecting agent 48.49 . Other studies examined possible cognitive mechanisms for the impairments [50][51][52][53][54][55][56][57][58] .…”
Section: Naturally-occurring Urtismentioning
confidence: 99%